Porous carbon loaded nanometer silicon negative electrode and preparation method thereof

By electrochemically depositing in-situ growth of amorphous silicon on a porous carbon electrode template and performing carbon coating, a porous carbon-loaded nano-silicon anode was prepared, which solved the problems of low gram capacity and poor cycle performance of existing lithium-ion battery anode materials. , achieving high specific capacity and excellent electrochemical performance.

CN119340347APending Publication Date: 2025-01-21CNBM ZHEJIANG MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411888282.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The theoretical capacity of the existing lithium-ion battery negative electrode material graphite is low, and the volume expansion of the silicon-based negative electrode material during the lithiation and deliquification process leads to rupture of the SEI film, affecting the cycling performance.

Method used

Through the use of the first electrochemical sedimentary system on the porous carbon electrode template, the in original electrochemical deposition system is used to grow without fixed silicon, and the carbon covering the second electrochemical sedimentation system is used to prepare a porous carbon load nano -silicon negative electrode.

Benefits of technology

The high -ratio capacity and excellent electrochemical properties are achieved, while avoiding the use of flammable and explosive gas, and improving production safety and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340347A_ABST
    Figure CN119340347A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon-loaded nano-silicon negative electrode and a preparation method thereof. According to the method, amorphous silicon grows in situ on a porous carbon electrode template based on electrochemical deposition of a first electrochemical deposition system, and carbon coating is carried out again by using a second electrochemical deposition system, so that the porous carbon-loaded nano-silicon negative electrode is obtained. The silicon-carbon negative electrode for the lithium ion battery is safely prepared by utilizing an electro-deposition technology, the porous carbon is firstly prepared into the negative electrode piece, silicon is deposited into the porous carbon by utilizing the electro-deposition technology, and the prepared silicon-carbon negative electrode can obtain excellent electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery energy storage and electrochemical deposition, and in particular to a porous carbon-loaded nano-silicon negative electrode and a preparation method thereof. Background Art

[0002] In recent years, with the vigorous development of electric vehicles and energy storage industries, the lithium-ion battery industry has achieved vigorous development. At the same time, the market's requirements for the performance of lithium-ion batteries are getting higher and higher. Graphite is currently the mainstream negative electrode material for lithium-ion batteries. However, graphite has an extremely low theoretical gram capacity of only 372mAh, which is increasingly unable to meet people's requirements for high-capacity batteries. The development of higher-capacity negative electrode materials has become an urgent need in the industry.

[0003] Silicon, as an element with a huge content in the earth's crust, has attracted the attention of many researchers. Silicon has the advantages of high theoretical specific capacity (3725mAh / g), low chemical potential, and no lithium dendrites during the charge and discharge process. It is considered by researchers to be a next-generation negative electrode material with great prospects. However, the disadvantages of silicon-based negative electrode materials are also very obvious: since silicon is a semiconductor material, its electrical conductivity is poor; the huge volume expansion during lithiation and delithiation causes the rupture of the SEI film, which in turn causes the battery cycle performance to deteriorate.

[0004] People try to solve the above problems through structural design and surface treatment. The most common structure is the core-shell structure design. Studies have shown that when the particle size of silicon is reduced to below 150nm, the volume effect during the lithiation process will no longer cause the material to break. The most direct way to reduce the particle size of the material is grinding, but the cost of grinding the material to below 150nm is huge. The nano-silicon obtained by grinding is very easy to agglomerate, and silicon and carbon are difficult to effectively combine by simple mixing, resulting in the first effect and performance of the material not meeting the requirements. And the raw material of the grinding method uses crystalline silicon as the raw material. During the charge and discharge process, the crystalline silicon powder undergoes an irreversible lithiation reaction with lithium ions, resulting in a low first efficiency of the material and affecting the cycle stability of the material. In order to avoid the occurrence of this reaction, the silicon in the silicon-carbon negative electrode material should be guaranteed to be amorphous silicon to the greatest extent.

[0005] Depositing silicon into porous carbon by chemical vapor deposition can effectively solve the problem of silicon-carbon interface contact. At the same time, the deposited silicon particle size is smaller, reaching 2-5nm. The volume expansion effect of the material can be effectively alleviated. The SCC55 silicon-carbon negative electrode material technology launched by G14 in the United States (Chinese patent application CN116978701A, published on October 31, 2023) discloses that silicon is deposited into a porous carbon material by chemical vapor deposition (CVD), and then a layer of carbon material is coated on the surface to achieve ultra-high capacity and first efficiency. However, due to the use of high-purity silane gases and acetylene and other flammable and explosive gases in the material preparation process. The material preparation process will inevitably bring about greater safety hazards and increase the cost of safe production. In current research, people have tried to use various deposition techniques to deposit silicon on the surface or inside of carbon, but there is currently no precedent for using electrochemical deposition technology (EVD), especially electrochemical deposition on negative electrode materials to grow amorphous silicon in situ. Silicon-carbon composite negative electrode (pole piece or material). Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a porous carbon-loaded nano-silicon negative electrode, which in situ grows amorphous silicon on a porous carbon electrode template based on electrochemical deposition of a first electrochemical deposition system, and carbon-coates it again using a second electrochemical deposition system; another purpose of the present invention is to provide a porous carbon-loaded nano-silicon negative electrode prepared using the aforementioned method; another purpose of the present invention is to provide a lithium battery product prepared using the porous carbon-loaded nano-silicon negative electrode.

[0007] Technical solution: In order to achieve the above-mentioned invention object, the present invention provides a method for preparing a porous carbon-loaded nano-silicon negative electrode, comprising:

[0008] Constructing a first electrochemical deposition system, the first electrochemical deposition system comprising a working electrode, a first counter electrode and a silicon precursor ionic liquid; the working electrode is prepared by loading porous carbon on a metal foil; the silicon precursor ionic liquid comprises a silicon source, an ionic liquid, an ionic liquid solvent and a phase transfer catalyst; the first electrochemical deposition system prepares a silicon-deposited porous carbon electrode under the action of a first electric field strength;

[0009] A second electrochemical deposition system is constructed, wherein the second electrochemical deposition system includes the silicon-deposited porous carbon electrode as a working electrode, a second pair of electrodes, and an organic solvent electrolyte; the second electrochemical deposition system prepares a carbon-coated porous carbon-loaded nano-silicon negative electrode under the action of a second electric field strength.

[0010] Furthermore, the first pair of electrodes and the second pair of electrodes are independently selected from graphite electrodes or Pt electrodes. As a preferred embodiment of the present invention, both the first pair of electrodes and the second pair of electrodes are graphite electrodes, which have the advantages of low price and stable properties.

[0011] Furthermore, the first electrochemical deposition system includes a three-electrode module consisting of the working electrode, the Pt electrode and the Ag / AgCl reference electrode; the second electrochemical deposition system includes a two-electrode module consisting of the silicon-deposited porous carbon electrode and the graphite electrode.

[0012] Furthermore, the first electric field strength is -0.1~-2.5V, and the electrochemical deposition time is 1-10h. As a preferred embodiment of the present invention, the first electric field strength is -1.2~-1.8. The dehydrogenation reaction of silane relative to carbon begins at a field strength of about E=-0.4V, and reaches an ideal state at about -1.6V. In addition to solving the problem of how to deposit silicon, the present invention also requires the problem of silicon deposition location. During the deposition process, silane needs to be adsorbed inside the pores of porous carbon, and then decomposed to undergo a deposition reaction. The present invention uses the dual effects of a phase transfer catalyst and an electric field to allow silane to adsorb and react on porous carbon, and finally deposit to obtain amorphous silicon.

[0013] As a preferred solution of the present invention, the organic solvent electrolyte includes but is not limited to any one or more combinations of methanol, ethanol, acetone, and tetrahydrofuran. Furthermore, the organic solvent electrolyte is ethanol, which has a more suitable chemical site.

[0014] Under high pressure, the electrolysis of organic solutions to prepare carbon films has been widely confirmed. The present invention utilizes this principle to deposit another layer of amorphous carbon on the surface of deposited silicon. This is beneficial to the protection of silicon by the electrode, avoiding direct contact between silicon and the electrolyte in the battery, and increasing the conductivity of the electrode. As a preferred embodiment of the present invention, the second electric field strength is a constant DC voltage of 1000-3000V. As a further optimization of the present invention, the second electric field strength is 1000-1500V.

[0015] Furthermore, the ionic liquid includes but is not limited to any one or more combinations of [BMP]TFSI, BMI(BF4), BMI(CF3SO2)2N, and BMI(PF6).

[0016] Furthermore, the ionic liquid phase transfer catalyst includes, but is not limited to, any one or more combinations of tetrabutylammonium chloride, tetrabutylammonium iodide, tetrabutylphosphine chloride, tetrabutylphosphine iodide and hexadecyltrimethylammonium bromide.

[0017] Furthermore, the ionic liquid solvent includes but is not limited to any one or more combinations of ethylene carbonate, acetonitrile, tetrahydrofuran, and sulfolane.

[0018] Further, the concentration of the silicon precursor ionic liquid in the solvent is 0.05-1 M. Preferably, the concentration of the ionic liquid is any concentration between 0.5-0.8M.

[0019] Furthermore, the silicon source is selected from any one or more combinations of SiH4, SiHCl3, SiCl4, and disilane. The present invention combines the silicon source into the liquid phase, and compared with the traditional CVD, the silane is no longer directly exposed to high temperature, and the production is safer and more reliable. As one of the optional implementations, when the technical solution of the present invention is used for industrial large-scale production, a gas distributor can be used to continuously provide a silicon-based solution. Preferably, the concentration of the silicon source is any concentration between 0.01-1M.

[0020] As a preferred solution of the present invention, the silicon source is SiH4, and the concentration after dissolution is 0.1-1 M. As a further optimization of the present invention, the concentration of SiH4 is 0.2-0.8 M; the most preferred concentration is 0.5M.

[0021] Furthermore, the metal foil is copper foil, and the porous carbon supported on the metal foil includes any one or more combinations of asphalt-based porous carbon, biomass-based porous carbon, phenolic resin-based porous carbon, and sugar-based porous carbon. Preferably, biomass-based porous carbon is used as a precursor.

[0022] Further, the porous carbon is mixed with a binder, a conductive agent, and deionized water and coated on a copper foil, and heated and vacuum dried to obtain a working electrode loaded with porous carbon. As a preferred embodiment of the present invention, the mass ratio of the porous carbon, the binder, and the conductive agent is (8-48): 1: 1, and the solid content after adding deionized water is 12-25wt%. As a further optimization of the present invention, the mass ratio of the porous carbon, the binder, and the conductive agent is 80: 10: 10, and the solid content after adding deionized water is 15wt%. The heating and drying is preferably carried out at 70-120°C, preferably at 80°C in vacuum (vacuum degree -10Pa) for 12h.

[0023] Furthermore, the binder includes any one or more combinations of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride.

[0024] Furthermore, the conductive agent includes any one or more combinations of carbon black, carbon nanotubes, graphene oxide, and graphene.

[0025] Furthermore, the porous carbon has 200-2000m 2 / g specific surface area; the pore volume of the porous carbon is 0.5-1.2cm 3 / g. As a preferred embodiment of the present invention, the porous carbon has a thickness of 0.5-1.0 cm 3 The pore volume of the porous carbon is 0.8 cm / g. The size of the pore volume directly affects the amount of silicon deposition and the saturated deposition ratio, and has a crucial impact on the performance of the material. 3 / g.

[0026] Furthermore, the mass ratio of silicon to carbon in the silicon-deposited porous carbon electrode is 0.01:1-2:1.

[0027] The porous carbon-loaded nano-silicon negative electrode prepared by the above method comprises at least:

[0028] Metal foil; The porous carbon layer supported on the surface of the metal foil has a thickness of 0.5-1.2 cm 3 / g pore volume; amorphous silicon deposited in situ in the porous carbon layer; and A carbon coating layer coated on the surface of the porous carbon layer.

[0029] Wherein, the mass of the deposited carbon is measured by a quartz crystal microbalance, and the ratio of the deposited mass of the carbon in the negative electrode to the total mass of the negative electrode is 1:100-10:100.

[0030] The present application also proposes a lithium battery, which includes: a positive electrode, a negative electrode, a separator and a lithium battery electrolyte; the negative electrode is the porous carbon-loaded nano-silicon negative electrode described above.

[0031] As a preferred embodiment, the lithium battery electrolyte includes a lithium salt and a non-aqueous solvent; the lithium salt includes any one or more combinations of LiPF6, LiClO4, LiBF4, and LiFSI; the non-aqueous solvent includes any one or more combinations of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate.

[0032] Beneficial effects: The present invention utilizes the electrodeposition technology to safely prepare silicon-carbon negative electrodes for lithium-ion batteries. The porous carbon is first prepared into a negative electrode sheet, and silicon is deposited into the porous carbon using the electrodeposition technology. The prepared silicon-carbon negative electrode can not only achieve excellent electrical properties. The silicon deposition process also does not involve high-temperature cracking operations of flammable and explosive gases, and the preparation method is safe, efficient, and has lower energy consumption. This invention has opened up a new path for the application of silicon-carbon negative electrodes in lithium-ion batteries. When the electrode is applied to lithium-ion batteries, it exhibits excellent performance. At the same time, since the production process does not involve the thermal decomposition of flammable and explosive gases, the safety problem in the production process of silicon-carbon negative electrodes is well solved.

[0033] Abbreviations and definitions used in this application CMC: sodium carboxymethyl cellulose; [BMP]TFSI: 1-butyl-4-methylpyridinium bis(trifluoromethanesulfonimide); BMI(BF4): 1-butyl-3-methylimidazolium tetrafluoroborate; BMI(CF3SO2)2N: 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; BMI(PF6): 1-butyl-3-methylimidazolium hexafluorophosphate; Tetrabutylammonium chloride: TBAC (Tetrabutylammonium chloride); Tetrabutylammonium iodide: TBAI (Tetrabutylammonium iodide); Tetrabutylphosphonium chloride: Tetrabutylphosphonium chloride; Tetrabutylphosphonium iodide: Tetrabutylphosphonium iodide; Hexadecyltrimethylammonium bromide: CTAB (Hexadecyltrimethylammonium bromide). BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The first cycle charge and discharge curve of the lithium ion battery prepared by using the porous carbon-loaded nano-silicon negative electrode of Example 2;

[0035] Figure 2 The first cycle charge and discharge curve of the lithium ion battery prepared by using the porous carbon-loaded nano-silicon negative electrode of Example 3;

[0036] Figure 3 The charge and discharge curve of the first cycle lithium ion battery prepared by using the porous carbon-supported nano-silicon negative electrode of Example 4;

[0037] Figure 4 This is the SEM image of the electrode in Example 2 after charging and discharging. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with embodiments and drawings.

[0039] Example 1

[0040] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0041] 1) 10 g of biomass-based coconut shell porous carbon was used as the precursor, where the pore volume of the precursor was 0.8 cm3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0042] 2) Dissolve [BMP]TFSI in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and TBAC in the [BMP]TFSI ionic liquid solution with concentration ratios of 0.2 M and 0.2 M, respectively.

[0043] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) and the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 4 hours to prepare a silicon-deposited porous carbon electrode.

[0044] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 2 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-1).

[0045] Example 2

[0046] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0047] 1) 10 g of biomass-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690 m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 20 wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0048] 2) Dissolve BMI (BF4) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and TBAC in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0049] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0050] 4) After washing the silicon-deposited porous carbon electrode prepared in step 3), it was combined with a graphite electrode and ethanol to form a second electrochemical deposition system, and electro-deposited at a voltage of 2500V for 3 hours to obtain a carbon-coated porous carbon-loaded nano-silicon negative electrode (SC-2). The first cycle charge and discharge curve of the lithium-ion battery prepared with the porous carbon-loaded nano-silicon negative electrode is shown in the figure below. Figure 1 The SEM images of the electrodes after charge and discharge are shown in Figure 4 shown.

[0051] Example 3

[0052] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0053] 1) 10 g of biomass-based porous carbon was used as the precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 92:4:4, and finally deionized water was added until the solid content reached 20wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0054] 2) Dissolve BMI (BF4) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and TBAC in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M, respectively.

[0055] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0056] 4) After washing the silicon-deposited porous carbon electrode prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electrochemical deposition was performed at a voltage of 2500V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-3). The first cycle charge and discharge curve of the lithium-ion battery prepared with the porous carbon-loaded nanosilicon negative electrode is shown in Figure 2. Figure 2 shown.

[0057] Example 4

[0058] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0059] 1) 10 g of biomass-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0060] 2) Dissolve BMI (BF4) in ethylene carbonate solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and TBAC in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M, respectively.

[0061] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 8 hours to prepare a silicon-deposited porous carbon electrode.

[0062] 4) After washing the silicon-deposited porous carbon electrode prepared in step 3), it was combined with a graphite electrode and ethanol to form a second electrochemical deposition system, and electro-deposited at a voltage of 1500V for 3 hours to obtain a carbon-coated porous carbon-loaded nano-silicon negative electrode (SC-4). The charge and discharge curve of the lithium-ion first-cycle battery prepared with a porous carbon-loaded nano-silicon negative electrode is shown in the figure below. Figure 3 shown.

[0063] Example 5

[0064] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0065] 1) 10 g of biomass-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0066] 2) Dissolve BMI (BF4) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and CTAB in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0067] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 7 hours to prepare a silicon-deposited porous carbon electrode.

[0068] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-5).

[0069] Example 6

[0070] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0071] 1) 10 g of biomass-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0072] 2) Dissolve BMI (BF4) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiHCl3 and TBAC in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0073] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 7 hours to prepare a silicon-deposited porous carbon electrode.

[0074] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-6).

[0075] Example 7

[0076] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0077] 1) 10 g of resin-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.75 cm 3 / g, specific surface area is 1823m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0078] 2) Dissolve BMI (PF6) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiHCl3 and TBAI in the BMI (PF6) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M, respectively.

[0079] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.8V for 8 hours to prepare a silicon-deposited porous carbon electrode.

[0080] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-7).

[0081] Example 8

[0082] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0083] 1) 10 g of resin-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.75 cm 3 / g, specific surface area is 1823m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on a copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0084] 2) Dissolve BMI (PF6) in ethylene carbonate solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiHCl3 and TBAC in the BMI (PF6) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M, respectively.

[0085] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.8V for 8 hours to prepare a silicon-deposited porous carbon electrode.

[0086] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-8).

[0087] Example 9

[0088] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0089] 1) 10 g of resin-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.75 cm 3 / g, specific surface area is 1823m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on a copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0090] 2) Dissolve [BMP]TFSI in ethylene carbonate solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiHCl3 and CTAB in the [BMP]TFSI ionic liquid solution with concentration ratios of 0.2 M and 0.2 M, respectively.

[0091] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.8V for 8 hours to prepare a silicon-deposited porous carbon electrode.

[0092] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-9).

[0093] Example 10

[0094] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0095] 1) 10 g of resin-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.9 cm 3 / g, specific surface area is 2033m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours. A porous carbon electrode template was obtained.

[0096] 2) Dissolve BMI (PF6) in ethylene carbonate solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and CTAB in the BMI (PF6) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0097] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0098] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 1500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-10).

[0099] Embodiment 11

[0100] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0101] 1) 10 g of petroleum coke-based porous carbon was used as a precursor, where the pore volume of the precursor was 1.0 cm 3 / g, specific surface area is 2106m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 20wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours to obtain a porous carbon electrode template.

[0102] 2) Dissolve BMI (BF4) in acetonitrile solvent to prepare an ionic liquid solution with a concentration of 1 M. Disilane and TBAI are dissolved in the BMI (BF4) ionic liquid solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0103] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0104] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 1500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-11).

[0105] Example 12

[0106] This embodiment provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0107] 1) 10 g of biomass-based porous carbon was used as a precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 20wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours to obtain a porous carbon electrode template.

[0108] 2) Dissolve BMI(CF3SO2)2N in acetonitrile solvent to prepare an ionic liquid solution with a concentration of 1 M. Disilane and TBAI are dissolved in the BMI(CF3SO2)2N ionic liquid solution with concentration ratios of 0.5 M and 0.1 M, respectively.

[0109] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.6V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0110] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 1500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-12).

[0111] Comparative Example 1

[0112] This comparative example provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0113] 1) 10 g of biomass-based coconut shell porous carbon was used as the precursor, where the pore volume of the precursor was 0.8 cm 3 / g, specific surface area is 1690m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10 and mixed, and finally deionized water was added until the solid content reached 15wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours to obtain a porous carbon electrode template.

[0114] 2) Dissolve SiH4 and TBAC in tetrahydrofuran solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0115] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E=-1.5V for 5 hours to prepare a porous carbon electrode with deposited silicon.

[0116] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 2000 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-13).

[0117] Comparative Example 2

[0118] This comparative example provides a porous carbon-loaded nano-silicon negative electrode, and the preparation method is as follows:

[0119] 1) 10 g of biomass-based porous carbon was used as the precursor, where the pore volume of the precursor was 0.3 cm 3 / g, specific surface area is 853m 2 / g. CMC and conductive carbon black were added in a mass ratio of 80:10:10, and finally deionized water was added until the solid content reached 20wt%. After mixing and stirring for 4 hours, the mixture was coated on copper foil and vacuum dried at 80°C for 12 hours to obtain a porous carbon electrode template.

[0120] 2) Dissolve BMI (BF4) in tetrahydrofuran solvent to prepare an ionic liquid solution with a concentration of 1 M. Dissolve SiH4 and TBAC in the BMI (BF4) solution with concentration ratios of 0.5 M and 0.1 M respectively.

[0121] 3) The electrode template obtained in step 1) is assembled with the silicon precursor obtained in step 2) as well as the Ag / AgCl reference electrode and the Pt electrode into a first electrochemical deposition system, and the electrodeposition is performed under an electric field of E = -1.6 V for 5 hours to prepare a silicon-deposited porous carbon electrode.

[0122] 4) After washing the porous carbon electrode of silicon-deposited silicon prepared in step 3), a second electrochemical deposition system was formed with a graphite electrode and ethanol, and electro-deposition was performed at a voltage of 1500 V for 3 hours to obtain a carbon-coated porous carbon-loaded nanosilicon negative electrode (SC-14).

[0123] Test Example 1

[0124] This test example provides a lithium battery, which can be prepared by using the porous carbon-loaded nano-silicon negative electrode obtained in Examples 1-12, together with a counter electrode, a separator and a lithium battery electrolyte.

[0125] The lithium battery electrolyte includes 1 mol / L LiPF6 dissolved in a mixed solvent system of diethyl carbonate and ethylene carbonate in a volume ratio of 1:1. The counter electrode is selected from a lithium sheet, and the diaphragm is selected from Celgard 2500 (PP diaphragm). The positive electrode shell, sample electrode sheet, diaphragm, lithium sheet, and nickel mesh negative electrode shell are assembled into a CR2016 button lithium-ion battery by a stacking method.

[0126] Test Example 2

[0127] This test example provides a lithium battery. The porous carbon-loaded nano-silicon negative electrode obtained in Example 1-12 and Comparative Example 1-2 is cut into negative electrode sheets with a diameter of 12 mm using a tablet press, and weighed for later use.

[0128] Battery assembly: stack the positive electrode shell, sample electrode, diaphragm, lithium sheet, nickel mesh, and negative electrode shell in a glove box. Add an appropriate amount of electrolyte in the middle of each sample. Add 100μL in total. Put the assembled button battery on the tablet press and press at 50MPa for 10s to obtain the button battery prepared by the sample.

[0129] Battery test: The battery test is carried out on the Blue Power multi-function battery test system, equipment model: CT2000A. The test steps are as follows: Shelf: 12h; Constant current discharge: 0.2C, (1C = 1000mAh), to 0.005V; Shelf time: 30min; Constant current charging: 0.2C, (1C = 1000mAh), to 1.5V; Shelf life: 30min.

[0130] Table 1 Material properties of various embodiments and comparative examples

[0131] Material Name Reversible capacity (mAh / g) First efficiency (%) SC-1 1440.28 88.84 SC-2 1520.35 90.88 SC-3 1375.44 84.23 SC-4 1350.23 83.36 SC-5 1365.66 82.45 SC-6 1379.65 80.46 SC-7 1465.33 80.36 SC-8 1483.26 88.21 SC-9 1354.33 86.32 SC-10 1450.65 80.44 SC-11 1635.66 83.23 SC-12 1796.32 81.88 SC-13 632.28 39.56 SC-14 1232.22 71.65

[0132] Experimental conclusion: The porous carbon-loaded nano-silicon negative electrode prepared by the electrodeposition method provided by the present invention can successfully prepare a silicon-carbon negative electrode for lithium-ion batteries, among which SC-2 exhibits excellent reversible capacity and first efficiency, exceeding 90%; and the first efficiency of the battery obtained by the negative electrode provided in the other embodiments is above 80%. In the present invention, the addition of ionic liquid plays a vital role in the deposition effect, and can effectively deposit silicon into the material voids. In Comparative Example 1 (SC-13), no ionic liquid was added, and the first efficiency and capacity of the material were far below expectations. Another crucial parameter is the pore volume and specific surface area of ​​the material. Porous carbon materials require sufficiently large pore volume and specific surface. In Comparative Example 2, due to the insufficient pore volume of the material, the amount of silicon that the material can accommodate is insufficient, resulting in the reversible capacity and specific surface area of ​​the material being far lower than the optimal solution.

[0133] The inventors have done a lot of work in optimizing the process. The inventors further identified that the type of porous raw materials also has a significant impact on the material properties. Compared with resin-based and petroleum coke-based materials, the deposition effect of biomass materials is significantly better. SC-8 and SC-11 use resin-based and petroleum coke-based porous carbon as raw materials, respectively, and the performance of the materials is somewhat different from the optimal solution. It is worth mentioning that the optimal preparation conditions for each product will be different. For example, when biomass porous carbon is used as raw material, the best solvent is tetrahydrofuran; and for resin-based porous carbon, the best solvent is ethylene carbonate. In addition, the experimental parameters also have a certain influence on the material properties. The product performance of Examples 3 and 5 is already very close to the optimal solution. However, due to differences in parameter ratios or types of ionic liquids, there is a certain gap compared to the solution.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous carbon-loaded nano-silicon negative electrode, characterized in that: Constructing a first electrochemical deposition system, the first electrochemical deposition system comprising a working electrode, a first counter electrode and a silicon precursor ionic liquid; the working electrode is prepared by loading porous carbon on a metal foil; the silicon precursor ionic liquid comprises a silicon source, an ionic liquid, an ionic liquid solvent and a phase transfer catalyst; The first electrochemical deposition system prepares a silicon-deposited porous carbon electrode under the action of a first electric field strength; A second electrochemical deposition system is constructed, wherein the second electrochemical deposition system includes the silicon-deposited porous carbon electrode as a working electrode, a second pair of electrodes, and an organic solvent electrolyte; the second electrochemical deposition system prepares a carbon-coated porous carbon-loaded nano-silicon negative electrode under the action of a second electric field strength.

2. The method for preparing a porous carbon-loaded nano-silicon negative electrode according to claim 1, characterized in that: The first pair of electrodes and the second pair of electrodes are independently selected from graphite electrodes or Pt electrodes.

3. The method for preparing a porous carbon-supported nano-silicon negative electrode according to claim 1 or 2, characterized in that: The first electrochemical deposition system comprises a three-electrode module consisting of the working electrode, the Pt electrode and the Ag / AgCl reference electrode; The second electrochemical deposition system includes a dual-electrode module consisting of the silicon-deposited porous carbon electrode and a graphite electrode.

4. The method for preparing a porous carbon-supported nano-silicon negative electrode according to claim 3, characterized in that: The first electric field strength is -0.1~-2.5V, and the electrochemical deposition time is 1-10h.

5. The method for preparing a porous carbon-loaded nano-silicon negative electrode according to claim 4, characterized in that: The second electric field strength can dehydrogenate and reduce the organic solvent electrolyte into carbon, thereby depositing it on the surface of the working electrode.

6. A method for preparing a porous carbon-supported nano-silicon negative electrode according to any one of claims 1-2, 4-5, characterized in that: The ionic liquid includes any one or more combinations of [BMP]TFSI, BMI(BF4), BMI(CF3SO2)2N, and BMI(PF6).

7. The method for preparing a porous carbon-supported nano-silicon negative electrode according to claim 6, characterized in that: The ionic liquid phase transfer catalyst includes any one or more combinations of tetrabutylammonium chloride, tetrabutylammonium iodide, tetrabutylphosphine chloride, tetrabutylphosphine iodide and hexadecyltrimethylammonium bromide.

8. The method for preparing a porous carbon-loaded nano-silicon negative electrode according to claim 7, characterized in that: The ionic liquid solvent includes any one or more combinations of ethylene carbonate, acetonitrile, tetrahydrofuran, and sulfolane.

9. A method for preparing a porous carbon-supported nano-silicon negative electrode according to any one of claims 1-2, 4-5, characterized in that: The metal foil is copper foil, and the porous carbon loaded on the metal foil includes any one or more combinations of asphalt-based porous carbon, biomass-based porous carbon, phenolic resin-based porous carbon, and sugar-based porous carbon.

10. The method for preparing a porous carbon-supported nano-silicon negative electrode according to claim 9, characterized in that: The porous carbon is mixed with a binder, a conductive agent, and deionized water, and then coated on a copper foil, and heated and vacuum dried to obtain a working electrode loaded with porous carbon; the porous carbon has a thickness of 200-2000 m 2 / g specific surface area, pore volume of 0.5-1.2cm 3 / g.

11. A method for preparing a porous carbon-supported nano-silicon negative electrode according to any one of claims 1-2, 4-5, characterized in that: The organic solvent electrolyte includes any one or more combinations of methanol, ethanol, acetone, and tetrahydrofuran.

12. The porous carbon-supported nano-silicon negative electrode prepared by the method according to any one of claims 1 to 11, characterized in that: The negative electrode comprises: Metal foil; The porous carbon layer supported on the surface of the metal foil has a thickness of 0.5-1.2 cm 3 / g pore volume; amorphous silicon deposited in situ in the porous carbon layer; and A carbon coating layer coated on the surface of the porous carbon layer.

13. A lithium battery, characterized in that include: A positive electrode, a negative electrode, a separator and a lithium battery electrolyte; the negative electrode is the porous carbon-loaded nano-silicon negative electrode as claimed in claim 12.

14. A lithium battery according to claim 13, characterized in that: The lithium battery electrolyte includes a lithium salt and a non-aqueous solvent; the lithium salt includes any one or more combinations of LiPF6, LiClO4, LiBF4, and LiFSI; the non-aqueous solvent includes any one or more combinations of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate.

Citation Information

Patent Citations

  • Decomposition of silicon-containing precursors on porous scaffold materials

    CN116978701A

  • Method for preparing silicon-based nanowire anode material of lithium ion battery by direct electrodeposition of ionic liquid systems

    CN105789566A

  • Silicon-based composite negative electrode plate, preparation method, and lithium ion secondary battery

    CN107799723A

  • Silicene nanocomposite anode for lithium ion battery

    US20150364754A1

  • Ultrafast electroplating of carbon as a coating agents for lithium ion battery applications

    US20200274139A1

Cited By

  • Microcrystalline silicon-carbon composite material as well as preparation method and application thereof

    CN121065716A

  • Microcrystalline silicon-carbon composite material, and preparation method and application thereof

    CN121065716B

  • Preparation method of pre-lithiation-free low-cost high-first-effect composite coated nano silicon

    CN121617941A